2012
DOI: 10.1371/journal.pone.0050987
|View full text |Cite
|
Sign up to set email alerts
|

HP0197 Contributes to CPS Synthesis and the Virulence of Streptococcus suis via CcpA

Abstract: Streptococcus suis serotype 2 (SS2), a major swine pathogen and an emerging zoonotic agent, has greatly challenged global public health. The encoding proteins with unknown functions the bacterium encodes are an obstruction to studies of the pathogenesis. A novel surface protective antigen HP0197 is one of these proteins which have no sequence homology to any known protein. In the present study, the protein was determined to be involved in bacterial virulence through an evaluation of the isogenic mutant (Δhp019… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 72 publications
(89 reference statements)
1
31
0
Order By: Relevance
“…This is reminiscent of a functional study in Streptococcus pneumoniae, which showed that CcpA is a master regulator of catabolism and virulence (19). A notable impact on the capsule synthesis and virulence properties of S. suis has also been shown (20). The LC-MS-based metabolomics experiments in the present study suggested that CcpA is involved in the regulation of amino acid metabolism, which may affect the metabolic fitness and is in accordance with the findings of other studies (21).…”
Section: Discussionsupporting
confidence: 90%
“…This is reminiscent of a functional study in Streptococcus pneumoniae, which showed that CcpA is a master regulator of catabolism and virulence (19). A notable impact on the capsule synthesis and virulence properties of S. suis has also been shown (20). The LC-MS-based metabolomics experiments in the present study suggested that CcpA is involved in the regulation of amino acid metabolism, which may affect the metabolic fitness and is in accordance with the findings of other studies (21).…”
Section: Discussionsupporting
confidence: 90%
“…S. suis serotype 2 strain 05ZY (also known as SC-19) was isolated from the brain of a diseased piglet during the outbreak of S. suis diseases in China in 2005. The strain expresses muramidase-released protein, extracellular protein factor, and suilysin and is highly pathogenic to mice and pigs, causing STSLS (42,43). RAW264.7 mouse macrophage cells were purchased from ATCC (TIB-71) and maintained in Dulbecco's modified Eagle's medium supplemented with 10% fetal calf serum at 37°C and 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…A S. pneumoniae ccpA mutant shows reduced expression of the capsular polysaccharide locus (105) and is highly attenuated for mouse nasopharyngeal and lung infection (106). Indirect evidence that S. suis CcpA controls capsule biosynthesis came from analysis of the effect of a mutation in a virulence-associated surface protein on HPr phosphorylation at serine-46 (107). In S. mutans , the major cause of dental caries, a ccpA mutant produces more acid than its parent, grows better at low pH, and excretes acid more rapidly, indicating that CcpA normally holds the cariogenic potential of S. mutans in check when rapidly metabolizable carbon sources are in excess (108).…”
Section: Metabolite-responsive Global Regulators That Influence Virulmentioning
confidence: 99%